Hepatitis B vaccination with or without hepatitis B immunoglobulin at birth to babies born of HBsAg‐positive mothers prevents overt HBV transmission but may not prevent occult HBV infection in babies: a randomized controlled trial. Issue 11 (23rd April 2013) - Pande, C.; Sarin, S. K.; Patra, S.; Kumar, A.; Mishra, S.; Srivastava, S.; Bhutia, K.; Gupta, E.; Mukhopadhyay, C. K.; Dutta, A. K.; Trivedi, S. S.
Summary Vertical transmission of Hepatitis B virus HBV can result in a state of chronic HBV infection and its complications. HBV vaccination with or without hepatitis B immunoglobulin (HBIG) prevents transmission of overt infection to the babies. However, whether it also prevents occult HBV infection in babies is not known. Consecutive pregnant women of any gestation found to be HBsAg positive were followed till delivery, and their babies were included in the study. Immediately after delivery, babies were randomized to receive either HBIG or placebo in addition to recombinant HBV vaccine (at 0, 6, 10 and 14 weeks). The primary end‐point of the study, assessed at 18 weeks of age, was remaining free of any HBV infection (either overt or occult) plus the development of adequate immune response to vaccine. The babies were further followed up for a median of 2 years of age to determine their eventual outcome. Risk factors for HBV transmission and for poor immune response in babies were studied. Of the 283 eligible babies, 259 were included in the trial and randomized to receive either HBIG (n = 128) or placebo (n = 131) in addition to recombinant HBV vaccine. Of the 222 of 259 (86%) babies who completed 18 weeks of follow‐up, only 62/222 (28%) reached primary end‐point. Of the remaining, 6/222 (3%) developed overt HBV infection, 142/222 (64%) developed occult HBV infection, and 12/222 (5%) had no HBV infection but had poor immune response. All 6 overt infections occurred in the placebo group (P = 0.030), while occult HBV infections were more common in the HBIG group (76/106 [72%] vs. 66/116 [57%]; P = 0.025). This may be due to the immune pressure of HBIG. There was no significant difference between the two groups in frequency of babies developing poor immune response or those achieving primary end‐point. The final outcome of these babies at 24 months of age was as follows: overt HBV infection 4%, occult HBV infection 42%, no HBV infection but poor immune response 8% and no HBV infection with good immune response 28%. Women who were anti‐HBe positive were a low‐risk group, and their babies were most likely to remain free of HBV infection (occult or overt) and had good immune response to the vaccine. Maternal HBeAg‐positive status and negativity for anti‐HBe predicted not only overt but also any infection (both overt and occult) in babies. In addition, high maternal HBV DNA and treatment with vaccine alone were significant factors for overt HBV infection in babies. The current practice of administration of vaccine with HBIG at birth to babies born of HBsAg‐positive mothers is not effective in preventing occult HBV infection in babies, which may be up to 40%. Because the most important risk factors for mother‐to‐baby transmission of HBV infection are the replicative status and high HBV DNA level in mothers; it will be worthwhile investigating the role of antivirals and HBIG administration during pregnancy to prevent mother‐to‐child transmission of HBV infection.